Anti-tribocorrosion resistance of NiTi–CeO2 alloys fabricated by laser powder bed fusion. (February 2023) - Xu, Zezhou; Guo, Yunting; Liu, Yuting; Sha, Pengwei; Zhang, Jundong; Liang, Ping; Yu, Zhenglei; Zhang, Zhihui; Ren, Luquan
Abstract: Alloying treatment is a common method to enhance metallic properties, but its application in laser powder bed fusion (LPBF) is still very limited, especially for LPBF-NiTi alloys. Rare earth elements as common alloying elements have been used in the modification of different LPBF- metals. In the case of LPBF-NiTi alloy, the application of rare earth alloying is only for mechanical functionality, but its influence on anti-tribocorrosion resistance is always neglected. In this paper, SEM, EDS, EBSD and TEM were used to characterize the microstructure and composition of the two samples with and without CeO2 addition, and the anti-tribocorrosion resistance was studied in 3.5 wt% NaCl solution. The results show that the addition of 0.03% CeO2 can weaken the strong texture of LPBF-NiTi alloy in the direction of (001), but also plays a role in refining grain. Meanwhile, the formation of a new NiCe phase and lattice distortion was found in TEM. In addition, the addition of 0.03% CeO2 improves the anti-tribocorrosion resistance of LPBF-NiTi alloy in 3.5%NaCl solution significantly. Graphical abstract: Image 1 Highlights: The tribocorrosion resistence of LPBF-NiTi alloys were reported firstly. The addition of CeO2 can enhance the anti-tribocorrosion resistence of LPBF-NiTi alloy. The NiCe phase and the strengthening effect of grain refinement are the keys to improve the anti-tribocorrosion.